Indocyanine green fluorescence-guided laparoscopic hepatectomy versus conventional laparoscopic hepatectomy for hepatocellular carcinoma: A single-center propensity score matching study - Jianxi, Wang; Xiongfeng, Zou; Zehao, Zheng; Zhen, Zhao; Tianyi, Peng; Ye, Lin; Haosheng, Jin; Zhixiang, Jian; Huiling, Wang (Frontiers in Oncology, 2022)
Background Indocyanine green fluorescence-guided laparoscopic hepatectomy (ICG-guided LH) is increasingly used for the treatment of hepatocellular carcinoma (HCC). However, whether ICG-guided LH can improve surgical outcomes remains unclear. This study aimed to investigate the short-term outcomes and survival outcomes of ICG-guided LH versus common laparoscopic hepatectomy (CLH) for HCC. Methods We conducted a retrospective analysis of 104 ICG-guided LH and 158 CLH patients from 2014 to 2020 at our center. To avoid selection bias, 81 ICG-guided LH and 81 CLH cases were analyzed after 1:1 propensity score matching (PSM). The baseline data and results were compared between the two groups. Results The baseline characteristics of both groups were comparable after matching. There was a significant difference in operative time: longer in the ICG-guided LH group than in the CLH group (p=0.004). However, there was no significant difference in operative time in anatomical resection between the two groups (p=0.987). There was a significant difference in operative time in non-anatomical resection: longer in the ICG-guided LH group than in the CLH group (p=0.001). There were no significant differences in positive surgery margin, blood loss, blood transfusion rate, postoperative complication rate, postoperative length of hospital stay, mortality within 30 days, and mortality within 90 days. The ICG-guided LH group appeared to have a trend towards better overall survival (OS), but there was no significant difference in OS (P=0.168) and recurrence-free survival (RFS) (P=0.322) between the two groups. Conclusions Although ICG fluorescence-guided LH is a timelier procedure to perform, it is a safe and effective technique with the advantages of intraoperative positioning, low postoperative complication rates, and potential to improve OS.